2005
DOI: 10.1007/s11864-005-0030-1
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial chemotherapy of primary brain tumors

Abstract: Intra-arterial (IA) chemotherapy is a form of regional delivery to brain tumors, designed to enhance the intra-tumoral concentrations of a given drug, in comparison with the intravenous route. Drugs that are likely to benefit from IA delivery have a rapid systemic clearance and include carmustine and other nitrosoureas, cisplatin, carboplatin, etoposide, and methotrexate. Clinical studies have demonstrated activity of IA chemotherapy approaches for low- and high-grade gliomas, and for cerebral lymphomas. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…However, its high toxicity led to a reduction of the mean survival time of the animals. This result is in agreement with previous report suggesting that treatment with cisplatin is not appropriated in the management of brain tumor [23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, its high toxicity led to a reduction of the mean survival time of the animals. This result is in agreement with previous report suggesting that treatment with cisplatin is not appropriated in the management of brain tumor [23].…”
Section: Discussionsupporting
confidence: 94%
“…This low uptake of drugs did not result in a significant anti-tumor effect, as measured by the mean survival time of the rats. When IV administrations were combined to radiotherapy, only treatment with Lipoxal ™ (the liposomal formulation of oxaliplatin) improved slightly the therapeutic efficacy (P = 0.045) Our results with Fischer rats are in line with clinical trials on GBM patients treated with IV platinum where a modest therapeutic efficiency was reported [23]. It is noteworthy that cisplatin was the only drug to accumulate significantly in the brain tumor after IV procedure.…”
Section: Discussionsupporting
confidence: 83%
“…Figure Numerous studies have reported on the use of IA therapy. A variety of single agents have been utilized including nitrosoureas, platinum analogs, 5-FU, etoposide, or in combination with systemic chemotherapy 3 . IA administration techniques have also been used to deliver adenoviral 4 or HSV 5 vectors to human brain tumors in mice and rats with some evidence of inhibition of tumor growth.…”
Section: Resultsmentioning
confidence: 99%
“…79 To date, superselective intraarterial cerebral infusion has been successfully leveraged for the treatment of high-grade gliomas and retinoblastomas. 3,67,86 In large-vessel stroke, intraarterial delivery of neuroprotectants can occur prior to, or following, clot extraction. If an agent is delivered distal to a thrombus prior to recanalization, it will likely remain in the tissue bed until flow is restored.…”
Section: Intraarterial Neuroprotectant Deliverymentioning
confidence: 99%